Is it possible to prevent the birth of a child with autism? - Chuprikov A.P (Moscow State University of Psychology and Education, 2017)
Recovery of health in families planning a child and pregnancy support in families at risk of a child with autism are the necessary measures, which, along with the results of researching certain patterns in epigenetic inheritances of autism, lead scientists to conclusions about the possibility to reduce the future birth rate of such children. The results of studying of some of the patterns of epigenetic inheritance of autistic disorders are also lead scientists to those conclusions. A short review of the array of works related to the topic of preventing the birth of children with autism and the results of a study of an Ukrainian medical team that confirms the hypothesis about seasonality in births of autistic children are presented. Seasonality of the birth of children with autism and psychoorganic syndrome was studied, fluctuations in the birth of sick children throughout the year, highly reliable for those with autism (р<0,001). Some measures are offered to reduce the risk of ASD, primarily accompanying the family by a medical psychologist.